Renewable Gas The Transition to Low Carbon Energy Fuels - Abbess, Jo.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
The author looks at the prospects for a transition from natural gas to low carbon gas, which could take several decades, and at how this will depend on the evolution of the fossil fuel industry. She investigates the technologies and energy systems for making the best use of renewable gas resources.
Keywords: Environment; Renewable energy resources; Climate change; Industrial management -- Environmental aspects; Renewable energy sources; Alternate energy sources; Green energy industries; Energy industries; Sustainable development; Environmental policy; Environment; Sustainable Development; Environmental Politics; Sustainability Management; Climate Change/Climate Change Impacts; Renewable and Green Energy; Energy Economics; Electronic books